Estudo do potencial de degradação do herbicida diuron e seus metabólitos por bactérias isoladas de solo de canavial - Egea, Tássia Chiachio [UNESP] (2014)
Bioprospection of microorganisms from impacted environment by xenobiotic and expose them to a target contaminant, under controlled conditions, provides a detailed study of the local microbial ability to adapt, survive and remediate the environment. The purpose of this study was to isolate bacteria with potential to degrade the diuron herbicide from soil with a diuron historical application of five years. The isolation media were composed by glucose (control) and diuron (inductor means) separately as a carbon source. A number of 400 bacteria were isolated, and they were classified as 68% gram-positive and 32% gram-negative. Most isolates showed potential to degrade diuron from 10 to 30%, into five days ofcultivation in liquid medium, however bacteria of the genera Stenotrophomonas and Bacillus were able to degrade 87% and 68%, respectively. Variations in the culture medium showed the importance of the presence of a carbon source easily assimilated to improve the bacteria development and ability to degrade diuron. Bacterial cells immobilized in Ca-alginate showed no significant increase in the rate ofdiuron degradation. However, microcosms techniques (soil) were effective in increasing the herbicidal degradation potential. Microbial consortium conditions in the presence of bacteria and fungi presented the highest herbicide diuron degradation percentages in liquid cultivation, cell immobilized and microcosm. The degradation of the herbicide diuron by bacteria allowed the degradation pathway of the parent molecule in the environment, highlighting the formation ofmetabolites DCPMU, DCPU, 3,4-DCA, 3,4-CAC, 4-CA, 4-CAC and aniline. The results obtained from this study strongly suggests that the bacteria present in soil impacted with diuron have the potential to degrade the herbicide, however completely mineralization is provided by the action of local microbial population.